A systematic review on the beneficial effect of date palm (Phoenix dactylifera) consumption on energy metabolism - Wahab N.A.; Zulkifli N.F.; Shamaan N.A.; Hamid N.A.; Zahir N.N.M. (American Scientific Publishers, 2024)
Phoenix dactylifera (date palm) produces edible, sweet fruits. The fruits has been mentioned multiple times in Quran as a super food, for its nutritious and numerous medicinal properties. Phoenix dactylifera fruit has been served as a staple food for millions of people around the world since ancient times. Despite the availability of reports on Phoenix dactylifera fruit, robust documentation regarding energy metabolism of dates is still inadequate. Consequently, date palm is hardly recognized as an energy rich food. This systematic review aims to study the beneficial effects of Phoenix dactylifera fruits and its components on energy metabolism in vivo. Published relevant articles were searched in four electronically indexed databases-Science Direct, Ebscohost, Biomed Central, and PubMed without any language or publication status restriction from January 1997 to 2015. Bibliographies of screened studies, relevant reviews and manuscripts were also searched using Google Scholar. Data were reported in the form of a descriptive summary followed by systematic reviews, according to the PRISMA guidelines. There were only three articles included in the qualitative synthesis and discussed the effects of Phoenix dactylifera on energy metabolism. All articles focused on animal studies. This systematic review identified several articles that reported the effect of Phoenix dactylifera on the energy content. Date palm pulp was reported to contain high valuable nutritive values and can be a potential animal feed. Phoenix dactylifera was also shown to have similar energy content compared to a standard animal feed (corn grain) therefore, it also can be an alternative energy source for livestock. The study reported on energy mechanism pathways of Phoenix dactylifera remained inconclusive. In addition, there are still gaps. Hence, further studies are required to provide a comprehensive understanding on this matter. 2017 American Scientific Publishers All rights reserved.